2010
DOI: 10.1111/j.1469-0691.2009.02945.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae serotype b conjugate vaccine failure in twelve countries with established national childhood immunization programmes

Abstract: The present study describes the clinical and immunological features of children with Hib vaccine failure, who were identified through national surveillance between 1996 and 2001 in Europe, Israel and Australia. True vaccine failure was defined as invasive Hib disease occurring ≥2 weeks after one dose, given after the first birthday, or ≥1 week after ≥2 doses, given at <1 year of age. Of the 423 cases (representing 0.2 cases per 100,000 child-years at risk) reported, 330 (78%) had received three doses in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 40 publications
0
14
0
2
Order By: Relevance
“…Among children <5 years of age with invasive H. influenzae disease, almost 1 in 5 cases is still caused by Hib, a potentially preventable disease. Breakthrough cases of invasive disease following Hib vaccination have been reported in immunocompromised and healthy children ( 25 , 26 ); however, vaccine failures are rare, and additional vaccine doses have are an effective way to achieve protective antibody levels in such instances ( 25 ). Although Hib vaccination has notably decreased the incidence of invasive Hib disease in all age groups, this reduction has been greatest among young children ( 3 , 10 , 11 , 27 ), and most Hib cases now occur in older adults with concurrent conditions ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among children <5 years of age with invasive H. influenzae disease, almost 1 in 5 cases is still caused by Hib, a potentially preventable disease. Breakthrough cases of invasive disease following Hib vaccination have been reported in immunocompromised and healthy children ( 25 , 26 ); however, vaccine failures are rare, and additional vaccine doses have are an effective way to achieve protective antibody levels in such instances ( 25 ). Although Hib vaccination has notably decreased the incidence of invasive Hib disease in all age groups, this reduction has been greatest among young children ( 3 , 10 , 11 , 27 ), and most Hib cases now occur in older adults with concurrent conditions ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of invasive H. influenzae disease may actually have increased in recent years (227,229), but since Hib vaccine failure is rare (236), most invasive infections occur in the extreme ages of life and in patients with predisposing conditions (224,226,229,232).…”
Section: Haemophilus Influenzae In the Post-hib-vaccine Eramentioning
confidence: 99%
“…A study conducted in Lagos, showed that ¾ of the vaccines at the local government level were sub-potent with the situation failing to improve over the three-year study period 1 . Studies have also reported that improper vaccine storage leading to the administration of sub-potent vaccines may have been associated with outbreaks of vaccine preventable diseases in Israel 2 and several developing countries 3 . Poor handling and storage, cold chain deficiencies such as inadequate infrastructure, power shortages and poor maintenance are associated with vaccine wastage.…”
Section: Introductionmentioning
confidence: 99%